2006
DOI: 10.1063/1.2197447
|View full text |Cite
|
Sign up to set email alerts
|

Pentaquarks — a brief update

Abstract: We argue that recently reported light and narrow uudds pentaquark state requires modification of a naive quark model. On the other hand such a state is naturally accommodated in chiral soliton models. We briefly describe the logic behind such models and underline differences between Skyrme model and chiral quark soliton models. We discuss phenomenological and theoretical consequences of Θ + . Finally we comment on recent experimental reports from CLAS, LEPS and SVD-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…M.Praszalowicz [82] gave a top class review of the present status of search for pentaquarks. The subject was put by organizers among "Future projects", probably to emphasize that the status of pentaquarks is still uncertain.…”
Section: Miscellaneamentioning
confidence: 99%
“…M.Praszalowicz [82] gave a top class review of the present status of search for pentaquarks. The subject was put by organizers among "Future projects", probably to emphasize that the status of pentaquarks is still uncertain.…”
Section: Miscellaneamentioning
confidence: 99%
“…Even if the Θ + exists with positive parity, a width as narrow as 1 MeV is theoretically difficult to understand 40 . However, several new theoretical ideas were presented showing that such a narrow width is consistent with theory.…”
Section: The Problem Of the Widthmentioning
confidence: 99%
“…Using a two-state model, Lipkin showed 41 that the mass eigenstates of two pentaquarks (e.g., mixtures of the Jaffe-Wilczek model and the diquark-triquark model) can mix, resulting in one coupling strongly to KN decay (with a wide width) and one decoupling (with a narrow width). Another approach, this time with mixing between the octet and the 10, shown by Praszalowicz 40 , can suppress the width by a correction factor that depends on the value of the pion-nucleon Σ term. From a completely different angle, using the QCD string model, Suganuma et al showed 42 that the pentaquark does not just "fall apart" as predicted by the quark model, but must overcome a sizeable potential barrier to decay into a KN final state.…”
Section: The Problem Of the Widthmentioning
confidence: 99%
“…Thus any chiral soliton model calculation of the Θ + width that is based on identifying the transition matrix element from the axial current must be strongly doubted. Given that this identification is continuously employed in soliton motivated studies [9,10,11,12,13] of pentaquark widths and that the resultant claim for the existence of narrow exotic baryons is airily adopted to this day [14], it occurs highly necessary to be emphatic on the arguments of ref. [8].…”
Section: Introductionmentioning
confidence: 99%